From laissez–faire to organized groups – A short history of sustainable charcoal producer associations in Kenya and Zambia - Grouwels, Sophie; Kisoyan, P.; Kitema, A.; Wanjira, E.O.; Ziba, V. (CIFOR-ICRAF, 2021)
This publication is part of a series of briefs describing findings from the EU-funded Governing Multifunctional Landscapes Sustainable Woodfuel project, which aims to contribute to knowledge, options, and networks for more sustainable woodfuel value chains across Sub-Saharan Africa.